ANALISIS KINERJA DINAS PENDAPATAN DALAM PEMUNGUTAN PAJAK HOTEL, RESTORAN, DAN RETRIBUSI PELAYANAN PASAR - Candrawati, Ni Luh; Suputra, I G.D. Dharma (E-Jurnal Akuntansi, 2015)
This research was conducted in Gianyar District Revenue Office. This study aims to determine the level of economic, efficiency, and effectiveness of tax revenue, taxes restaurants and markets services levy Year 2008-2012. The results of this study the performance Giayar District Revenue Office to be reviewed based on the concept of Value for Money on hotel tax revenue, restaurant tax, and fees for the 2008-2012 service year market economies the average ratio of 86 percent can be categorized as economic, efficiency ratios mean means are 24,2 percent can be categorized as very efficient, and the average effectiveness ratio of 123,17 percent can be categorized as very effective. It can be said the performance of the Department of Revenue in the Gianyar regency hotel tax, restaurant tax, and levy service markets are in accordance with the concept of Value for Money.
Keywords: Public Sector Performance, Hotel Tax, Restaurant Tax, Levies Market Service, Value for Money